2016
DOI: 10.1371/journal.pone.0156197
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and Re-Engineering of Azotobacter vinelandii Alginate Lyase to Enhance Its Catalytic Efficiency for Accelerating Biofilm Degradation

Abstract: Alginate is known to prevent elimination of Pseudomonas aeruginosa biofilms. Alginate lyase (AlgL) might therefore facilitate treatment of Pseudomonas aeruginosa-infected cystic fibrosis patients. However, the catalytic activity of wild-type AlgL is not sufficiently high. Therefore, molecular modeling and site-directed mutagenesis of AlgL might assist in enzyme engineering for therapeutic development. AlgL, isolated from Azotobacter vinelandii, catalyzes depolymerization of alginate via a β-elimination reactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…EPS disruption strategies (including the use of alginate lyase) have, despite advances in enzyme engineering, so far proved ineffective. 31 More recently, products derived from the marine environment have been investigated for antimicrobial/anti-biofilm activity e.g., furanones from the red algae Delisea pulchra . 32 , 33 However, none of these potential therapeutic approaches are as yet in clinical use.…”
Section: Introductionmentioning
confidence: 99%
“…EPS disruption strategies (including the use of alginate lyase) have, despite advances in enzyme engineering, so far proved ineffective. 31 More recently, products derived from the marine environment have been investigated for antimicrobial/anti-biofilm activity e.g., furanones from the red algae Delisea pulchra . 32 , 33 However, none of these potential therapeutic approaches are as yet in clinical use.…”
Section: Introductionmentioning
confidence: 99%
“…CMO (choline monooxygenase) can catalyze the first step of glycine betaine synthesis [ 80 ], which indicates that glycine betaine can be used as an osmoprotectant in marine Oligoflexia as well. In addition, there are many genes involved in transport or transformation of sugar as osmoprotectant, such as malK , msmX , rgpF and algI genes in Oligoflexia ( Table 2 ) [ 81 , 82 , 83 , 84 ]. In light of all these results, betaine as an osmoprotectant is commonly used among different groups of Bdellovibrionota, all having a variety of genes for fitness in the ocean.…”
Section: Resultsmentioning
confidence: 99%
“…For example, the alginate lyase A1-III, which originated from Sphingomonas sp. A1, was used as a template to model the homology of another alginate lyase AlgL (Jang et al 2016). The binding structure of the AlgL-alginate complex showed that the substrate-binding cleft and the adjacent molecular surface of the enzyme were covered with positively charged residues (e.g., K 194 , K 245 and K 319 ).…”
Section: Rational Design Of Alginate Lyasementioning
confidence: 99%